Transient midventricular ballooning: a case report and review of the literature - Abuzetun, Jamil Y (BioMed Central, 2008)
BACKGROUND: We describe a case of transient left midventricular ballooning in 68-year-old male patient presented with picture of acute coronary syndrome. CASE PRESENTATION: The left ventriculogram showed mid ventricular akinesis and dilatation along with hypercontractile apex and basal segments. Follow up echocardiogram after one month showed resolution of wall motions abnormalities and normalization of the left ventricular function. CONCLUSION: This is considered as a new variant of previously reported transient left ventricular apical ballooning; the only difference in our case is the location of wall motions abnormalities.